Job rotation in beef packing operations: beyond the physical dimensions of work - Nascimento, Adelaide (2018)
Brazilian Regulation NR-36, specific to the slaughterhouse and meat packing industries, emphasizes the implementation of job turnover to reduce workers' exposure to repetitive and machine-controlled physical strain. However, studies have shown that the effects of such measures are generally less than expected, and that rotation alone is not the solution to work-related health problems. Based on a study performed in a beef packing plant, the article aims to present and discuss real work dimensions that are considered relevant to the plant workers' health and safety. Knowledge of such dimensions is important for the implementation of job rotation projects. The methodology included interviews with 16 volunteers divided into four groups. The focus group and collective confrontation techniques were used, drawing on videos of the work. The results pointed to dimensions already known in the literature, related to physical strain, the required skills, work pace, and insufficient time to perform quality work. New data appeared in relation to the work's heterogeneous specifications, representing a source of psychological pressure during work in the cattle slaughtering areas. These organizational dimensions impact workers' individual and collective activity as well as workplace health. In our view, and corroborating international studies, in addition to the work's physical dimensions, organizational, human, strategic, and pedagogical aspects should be considered in projects involving the implementation of job rotation.